Antiplatelet Agents Inhibit the Generation of Platelet-Derived Microparticles - Giacomazzi, Alice; Degan, Maurizio; Calabria, Stefano; Meneguzzi, Alessandra; Minuz, Pietro (Frontiers in Pharmacology, 2016)
Platelet microparticles (PMPs) contribute to thrombogenesis but the effects of antiplatelet drugs on PMPs generation is undefined. The present study investigated the cellular events regulating PMP shedding, testing in vitro platelet agonists and inhibitors. Platelet-rich plasma from healthy subjects was stimulated with arachidonic acid, U46619, collagen type-I (10 and 1.5 µg/mL), epinephrine, ADP or TRAP-6 and pre-incubated with acetylsalicylic acid (ASA, 100 and 10 µmol/L), SQ-29,548, apyrase, PSB-0739, or eptifibatide. PMPs were detected by flow-cytometry using CD61 and annexin-V as fluorescent markers. Platelet agonists induced annexin V-positive PMP shedding. The strongest response was to high concentration collagen. ADP-triggered PMP shedding was dose-independent. ASA reduced PMPs induced by arachidonic acid- (645, 347-2946 vs 3061, 446-4901 PMPs/µL; median ad range, n=9, P<0.001), collagen 10 µg/mL (5317, 2027-15935 vs 10252, 4187-46316 PMPs/µL; n=13, P<0.001), collagen 1.5 µg/mL (1078, 528-2820 vs 1465, 582-5948 PMPs/µL; n=21, P<0.001) and TRAP-6 (2008, 1621-2495 vs 2840, 2404-3031 PMPs/µL; n=3, P<0.01) but did not affect the response to epinephrine or ADP. The ADP scavenger apyrase reduced PMPs induced by U46619 (1256, 395-2908 vs 3045, 1119-5494 PMPs/µL, n=6, P<0.05), collagen 1.5 µg/mL (1006, 780-1309 vs 2422, 1839-3494 PMPs/µL, n=3, P<0.01) and TRAP-6 (904, 761-1224 vs 2840, 2404-3031 PMPs/µL, n=3, P<0.01). The TP receptor antagonist SQ-29,548 and the P2Y12 receptor antagonist PSB-0739 markedly inhibited PMPs induced by low doses of collagen. Except for high-dose collagen, eptifibatide abolished agonist-induced PMP release. Both TXA2 generation and ADP secretion are required as amplifiers of PMP shedding. The crucial role of the fibrinogen receptor and the collagen receptor in PMPs generation, independently of platelet aggregation, was identified.